Answer:
Explanation:
1. (x - 3)(x + 7) = 0
By zero product property,
(x - 3) = 0 ⇒ x = 3
(x + 7) = 0 ⇒ x = -7
2. (2x + 6)(x - 7) = 0
2(x + 3)(x - 7) = 0
By zero product property,
(x + 3) = 0 ⇒ x = -3
(x - 7) = 0 ⇒ x = 7
3). (4x - 2)(x + 4) = 0
2(2x - 1)(x + 4) = 0
(2x - 1) = 0 ⇒ x =
(x + 4) = 0 ⇒ x = -4
4. (5x - 1)(3x + 9) = 0
3(5x - 1)(x + 3) = 0
By zero product property,
(5x - 1) = 0 ⇒ x =
(x + 3) = 0 ⇒ x = -3
5. (x - 8)(x + 2) = 0
By zero product property,
(x - 8) = 0 ⇒ x = 8
(x + 2) = 0 ⇒ x = -2